2020
DOI: 10.1186/s12889-020-08624-6
|View full text |Cite
|
Sign up to set email alerts
|

Informal workplaces and their comparative effects on the health of street vendors and home-based garment workers in Yangon, Myanmar: a qualitative study

Abstract: Background: Globally, two billion workers are employed informally but there is limited research on the relationship between informal work and health. Existing studies have focused on informality as an employment condition, with little emphasis on the diversity of physical and social contexts in which informal work takes place. The study considers the diversity of informal workplaces and explores the ways in which this diversity might influence health and well-being of two informal occupational groups in Yangon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The results of the current study showed that the efforts to improve the health of informal workers should consider the contexts in which they work in order to develop tailored interventions for specific subpopulations of informal workers [ 25 ]. The results of this study showed that the work environment and lack of infrastructure are associated with ill health, and the interventions in responding to the findings were integrated within the proposed model.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the current study showed that the efforts to improve the health of informal workers should consider the contexts in which they work in order to develop tailored interventions for specific subpopulations of informal workers [ 25 ]. The results of this study showed that the work environment and lack of infrastructure are associated with ill health, and the interventions in responding to the findings were integrated within the proposed model.…”
Section: Resultsmentioning
confidence: 99%
“…PKL pada dasarnya merupakan kegiatan usaha sektor informal, sehingga keberadaannya berada diluar sistem perencanaan perkotaan yang umum. Posisi tersebut menjadikan keberadaan PKL pada umumnya tidak tertata, tidak higienis, tidak aestetik, dan rawan premanisme (Ko Ko Et Al., 2020). Sebagai akibatnya pemerintah kota DKI jakarta menjadi terpaksa harus melakukan penertiban sebagai jalan untuk mengembalikan fungsi ruang-ruang publik tersebut kepada fungsi awalnya (Rahardyan,Aziz & Fitriani, 2019).…”
Section: Pendahuluanunclassified
“…Informal vendors frequently operate from outdoor or street locations without a formal building structure, including tents, cartons, or mobile food trailers. These vendors conduct their business in public areas close to downtown streets, marketplaces, or parks (such as a storefront, a sidewalk, a roadside, or pavement) [6]. Some informal vendors, however, operate markets in discrete locations within an enclosed permanent brick structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some informal vendors, however, operate markets in discrete locations within an enclosed permanent brick structure. These vendors may operate in semi-public spaces, such as inside market buildings and public transportation stations [6], as well as train stations, taxi ranks, and other public places. The burden of disease associated with environmental exposures disproportionately impacts outdoor vendors in big cities all over the world.…”
Section: Introductionmentioning
confidence: 99%